Práticas de letramento no meio rural brasileiro: a influência do movimento sem terra em escola pública de assentamento de reforma agrária - CAMPOS, Samuel Pereira (Universidade Estadual de Campinas, 2018)
In this thesis we discuss the influence of Movimento Sem Terra (MST), understood as a discoursive communnity that acts institutional and intentionally at the brazilian rural workers formation, taking as reference its organization, social practices and ways of acting toward the social world. We focus our discussion at the literacy practices engendered in a public school, that reveals the influence of the Sem Terra literacy project in conflict with the school official project, broght into the researched school after its official establishment. As our research subjets were living diferent kinds of envolvement with the Sem Terra community, we assumed that researched school and the subjects involved in our field work, would present literacy practices related to the two projects in dispute in the school, characterized as emancipatory literacy project and schoolar literacy project, from the point of view of the new literacy studies. From this place, we analyse the educational project designed by MST, seen as an ideological, situated and emancipatoy literacy project (Street, 1984, 1995; Barton, 1998; Freire, 1978, 1987, 1995), and its influences over the literacy practices at the researched environment, focusing the two projects in conflict in the classroom of two Portuguese Language teachers, whose practices are representative of the two project in dispute at school.